ORGANISATIONAL CAPABILITIES, COMPETITIVE ADVANTAGE AND PERFORMANCE IN SUPPORTING INDUSTRIES IN VIETNAM - Nham Phong Tuan; Takahashi Yoshi (Asian Academy of Management Journal, 2010)
This paper focuses on applying the resource-based view (RBV) of firms to explain performance in supporting industries in Vietnam. Specifically, we based our research on the comprehensive framework of RBV and reviewed previous empirical researches before deciding on adopting a dynamic capabilities approach to test relationships among organisational capabilities, competitive advantage and performance. A multivariate analysis of survey responses of 102 firms belonging to supporting industries in Vietnam indicates that the organisational capabilities are related to the competitive advantage, that the competitive advantage is related to performance, and that the competitive advantage mediates the relationship between organizational capabilities and performance. These findings have considerable implications for academics as well as practitioners. Finally, this study also provides directions for future research.